Machine Translation Based on Neural Network: Challenge or Chance? - Minyun, Xu (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2023)
With the acceleration of economic globalization, there is a growing demand for translation services. In recent years, the quality of machine translation has been significantly improved. Compared with human translation, machine translation has the advantages of low cost and high speed. However, there is still little discussion on this scholarship, as this neural machine translation brings both convenience and pressure to translators. To address this issue, this paper will analyze the advantages and disadvantages of neural machine translation and discuss whether neural machine translation is a chance or a challenge for human translators.